Comparative analysis of continuous and interrupted suturing techniques for repair of episiotomy or second degree perineal tear - Samal, Sunil Kumar; Rathod, Setu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Perineal trauma is a serious and frequent problem after childbirth which is experienced by millions of women worldwide and the type of perineal repair may have an impact on pain and healing. The objective of this study was to assess the effects of continuous subcuticular versus interrupted transcutaneous sutures on women following episiotomy or second degree perineal repair following childbirth. Methods: A prospective comparative study comprising 141 women who had undergone vaginal deliveries with episiotomies or second-degree tearing of the perineum between August 2015 and July 2016Two groups were made among which one group was repaired with continuous, nonlocking sutures involving the vagina, perineum, and subcutaneous tissues and the other group had continuous, locking sutures of the vagina, interrupted sutures in the perineal muscles, and interrupted transcutaneous sutures. The threads used for stitching were identical in both groups i.e. rapidly absorbed polyglactin 910 suture material. Results: On the 2nd day after delivery, the perineal pain scores during lying, sitting and walking in the continuous technique(CT) group was less compared to the interrupted technique(IT) group(p value 0.009). On 10th day after delivery the perineal pain score during sitting and walking were statistically less (p value 0.027) in the CT group. On 42th day there was no difference in pain score between both the groups. The amount of suture materials consumed in CT group was statistically less than IT group(p<0.001). There was no difference in incidence of wound dehiscence (p value 0.301) but superficial dyspareunia is more in IT group which is statistically significant. Conclusions: The episiotomy and perineal tear repairs with continuous suturing associated with lesser incidence of short or long term pain, lesser requirement of suture material without an increase in complication than interrupted suturing.